Experimental Sensing and DFT Mechanism of Zn(II) Complex for Highly Sensitive and Selective Detection of Acetone - Mohd. Muddassir; Mohammad Usman; Abdullah Alarifi; Mohd. Afzal; Khulud Abdullah Alshali; Abeer Beagan; Abhinav Kumar; Naaser A. Y. Abduhd; Musheer Ahmad (Crystals, 2020)
In the present work, a new Zn(II) perchlorate complex with 2,2’–bipyridyl of formulation {[Zn(bipy)2(H2O)](ClO4)2} (1) was obtained and well analyzed. This chemosensor was evaluated as a selective sensor for acetone among the several different organic solvents(CH3OH, EtOH, i–PrOH, i–BuOH, CHCl3, CH2Cl2, CCl4, C6H6, C7H8, C8H10, C2H3N, C3H7NO, C4H8O2, C3H6O3) in a fluorescence turn–off response in accordance with theoretical calculations. Sensing experiments were performed at ambient temperature which shows the acetone molecule distinctly reduces transfer of energy barrier to complex 1 and hence, produces remarkable luminescent quenching. Also, the weak intermolecular hydrogen–bonding interactions thanks to the presence of various hydrogen bonding donors and acceptors, exist between ligand molecules, which were broken during fluorescence, resulting in quenching. The stoichiometry ratio and association constant were evaluated using Benesi–Hildebrand relation giving 1:1 stoichiometry between complex 1 and acetone. Additionally, DFT results can also explicate the significant response on complex 1 upon addition of acetone. This work is vital in a new loom for the detection of acetone and other ketones.